Student Teachers' Team Teaching during Field Experiences: An Evaluation by their Mentors. Issue 5 (19th October 2016) - Simons, Mathea; Baeten, Marlies
Abstract : Since collaboration within schools gains importance, teacher educators are looking for alternative models of field experience inspired by collaborative learning. Team teaching is such a model. This study explores two team teaching models (parallel and sequential teaching) by investigating the mentors' perspective. Semi-structured interviews were conducted in order to map their attitudes, the advantages and disadvantages they observe and the conditions for implementation. Results indicate that mentors adopt an open attitude toward team teaching. They observe advantages for all actors involved, especially for student teachers (e.g. support, professional growth) and learners (e.g. rich and varied lessons). The study corroborates the findings retrieved in the literature, enlarges and refines them, and gives a clearer view on the importance of each (dis)advantage.